B(3,-1)
Step-by-step explanation
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
Step 1
Point 1
(-2,0)
replace
![\begin{gathered} y=ax^2+bx+c \\ 0=a(-2)^2+b(-2)+c \\ 0=4a-2b+c \\ 2b-4a=c\rightarrow equation\text{ (1)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/q9517aas309kp29qiqcie3mfu02jxeydfi.png)
Point 2
(8,0)
![\begin{gathered} y=ax^2+bx+c \\ 0=a(8)^2+b(8)+c \\ 0=64a+8b+c\rightarrow equation\text{ (2)} \\ c=-64a-8b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/57vjguaqt5k3w1cm6h6flkpsgtj29nx2yr.png)
c) c= c, so
![\begin{gathered} 2b-4a=-64a-8b \\ -4a+64a=-8b-2b \\ 60a=-10b \\ (60a)/(-10)=(-10b)/(-10) \\ b=-6a \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/gt77bf4ytva4idi8mpbmx7fxihz19pm6xt.png)
Step 2
when the function is in the form
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
the vertex is given by
![(-(b)/(2a),f(-(b)/(2a))](https://img.qammunity.org/2023/formulas/mathematics/high-school/o8pji45qamoc2mqmtu48r6mw9fnxxqptmy.png)
so,replace
![\begin{gathered} -(b)/(2a) \\ -((-6a))/(2a)=(6a)/(2a)=3 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/19lbhnguqpiidbum1z7tb8riviz16nj987.png)
therefore, the component of the vertex is 3
let's check the options
A. (3,0)
B. (3,-1)
we can see that y component of option A is zero , it means (3,0 ) is a zero of the function, but we had already the zeros, therefore, we can discard this options,
in other words,
the answer is
B(3,-1)
I hope this helps you